2013
DOI: 10.1002/eji.201242947
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lgr5‐positive epithelial cells in the murine thymus

Abstract: Leucine-rich repeat-containing G protein-coupled receptor (Lgr)5 is a marker for epithelial stem cells in the adult intestine of mice. Lgr5 transcripts have also been detected in the developing murine thymus, leading to speculation that Lgr5 is a marker for the longsought stem cell of the thymus. To address the nature of the Lgr5-expressing thymic epithelial cells (TECs), we used Lgr5-GFP reporter mice. We show that epithelial cells expressing Lgr5 protein are present in the fetal thymus during a specific deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In 1998, Hsu et al ( 1 ) found that the leucine-rich repeat-containing G-protein coupled receptor 5 (Lgr5) was homologous to the gonadotropin and thyrotropin receptors in Drosophila ( 1 ). Lgr5 is expressed in the eye, brain, mammary glands, hair follicles, stomach, intestines and other tissues ( 2 , 3 ). Lgr5 serves an important role in the Wnt signaling pathway, which is intimately involved in tumor development ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 1998, Hsu et al ( 1 ) found that the leucine-rich repeat-containing G-protein coupled receptor 5 (Lgr5) was homologous to the gonadotropin and thyrotropin receptors in Drosophila ( 1 ). Lgr5 is expressed in the eye, brain, mammary glands, hair follicles, stomach, intestines and other tissues ( 2 , 3 ). Lgr5 serves an important role in the Wnt signaling pathway, which is intimately involved in tumor development ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the Wnt target genes LGR5 and LGR6, which are markers of several stem/progenitor cells 14 , 39 46 , were also positively expressed, especially LGR5, which is a liver-derived stem cell marker 13 , 15 . This LGR5 expression supports the potential use of hMSG-EpiPCs as a cellular basis for regenerative liver medicine.…”
Section: Discussionmentioning
confidence: 99%